2022
DOI: 10.3390/ijms23147800
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine plus Alcohol: What We Know and What We Can Expect about This

Abstract: Drug abuse has become a public health concern. The misuse of ketamine, a psychedelic substance, has increased worldwide. In addition, the co-abuse with alcohol is frequently identified among misusers. Considering that ketamine and alcohol share several pharmacological targets, we hypothesize that the consumption of both psychoactive substances may synergically intensify the toxicological consequences, both under the effect of drugs available in body systems and during withdrawal. The aim of this review is to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 189 publications
0
3
0
Order By: Relevance
“…In animal studies, ketamine has also been shown to induce hepatic CYP enzymes [ 11 , 12 ], including CYP2E1 which may potentiate toxicities from other medications such as ethanol and acetaminophen by increasing the concentration of their toxic metabolites [ 13 , 14 ]. The coingestion of ketamine with alcohol has been shown to increase the risk of hepatotoxicity [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, ketamine has also been shown to induce hepatic CYP enzymes [ 11 , 12 ], including CYP2E1 which may potentiate toxicities from other medications such as ethanol and acetaminophen by increasing the concentration of their toxic metabolites [ 13 , 14 ]. The coingestion of ketamine with alcohol has been shown to increase the risk of hepatotoxicity [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients involved in this review were rather young, which can be explained by the recreational nature of the ketamine abuse. Concomitant alcohol abuse is quite common in ketamine abuser population and can be up to 25% [ 28 ]. Due to the possible cytotoxic effect of ketamine on urothelium, patients often experience urinary symptoms [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NMDA receptors on GABAergic interneurons leads to disinhibition and activation of AMPA receptor pathways [31]. The pleiotropic nature of ketamine [32] is evident in this study by the different fits provided by its minimum energy conformer on the GTP template, which include those characteristic of SERT, glycine, GABA, NMDA, kainate and AMPA ligands (see Williams 2018, Figure 2) [33]. The wide spectrum of effects on cells produced by low ketamine concentrations, including oxidative stress and apoptosis, is of some concern in the clinical context [34].…”
Section: Discussionmentioning
confidence: 99%